Brand identity essentials 100 principles for designing logos and building brands - Budelmann, Kevin (Rockport Publishers, 2010)
This title outlines and demonstrates basic logo and branding design guidelines and rules through 100 principles including the elements of a successful graphic identity, identity programs and brand identity, and all the various strategies and elements involved.